(untitled) (American Journal of Islam and Society, 2016)
Brian T. Edwards’ book boasts of an insightful interdisciplinary approach that draws upon his expertise in anthropology, literary and cultural studies, American studies, and Middle Eastern and North African (MENA) studies. His approach and overall argument can benefit both the specialists in these disciplines and the non-academic audience interested in the MENA region’s contemporary cultural history and connection to the United States’ international cultural politics. Edwards introduces two principal concepts to formulate his arguments: the “ends of circulation” and “jumping publics.” In his view, the former describes “new contexts for American texts” and the latter explicates “the way culture moves through the world in the digital age” (p. 27). He offers four reasons why the circulation of cultural products “across borders and publics” is important to the contemporary American audience. First, “The U.S. Department of State has invested time and funding in propagating the circulation of American culture.” Second, “American media venues have a continuing interest in this topic, whether in the coverage of the Egyptian revolution or in the popular fascination with books such as Reading Lolita in Tehran (2003) that depict Americans or American culture displaced in the Middle East.” Third, many “popular and influential writers,” including “the developmentalist Daniel Lerner in the 1950s to Thomas Friedman in the 1990s and 2000s to media studies journalist Clay Shirky, assume a technocentric or cyberutopian determinism,” and thus consider “access to new technologies and media” and “modernization and freedom” inevitably intertwined. And fourth, “In the fields of American literary studies and comparative literature, the ways in which the American culture and literature are taken up around the world puts pressure on the ways of doing things in those disciplines” (p. 16) ...